2018
DOI: 10.1364/ol.43.002114
|View full text |Cite
|
Sign up to set email alerts
|

Isolated attosecond pulse in the water window from many-cycle laser-driven plasma mirrors without pulse engineering

Abstract: High-order harmonic generation from relativistic laser-driven plasma mirrors is an attractive route to produce highly energetic attosecond pulses in the extreme ultraviolet to x-ray regime. To achieve an isolated attosecond pulse (IAP) driven by many-cycle intense laser pulses, pulse engineering techniques such as polarization modulation and wavefront rotation, are usually needed. Here we show that it is possible to generate an IAP without pulse engineering. Through particle-in-cell simulations, it is found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Use of two counter-rotating circularly polarized laser fields has lead to the breakthrough of circularly polarized high harmonic [3][4][5] and isolated attosceond pulse [6] generation experimentally. Later, it was numerically demonstrated that circularly polarized XUV and attosceond pulses can also be generated via HHG from relativistic plasma surfaces [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Use of two counter-rotating circularly polarized laser fields has lead to the breakthrough of circularly polarized high harmonic [3][4][5] and isolated attosceond pulse [6] generation experimentally. Later, it was numerically demonstrated that circularly polarized XUV and attosceond pulses can also be generated via HHG from relativistic plasma surfaces [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism is generally described as relativistically oscillating mirrors (ROM) [22][23][24][25][26][27][28]. While HHG from ROM with controllable polarization [29][30][31][32][33][34] (i.e., beyond linear polarization) and vortex wavefront [35][36][37] (i.e., with orbital angular momentum, OAM) has been investigated intensively, HHG with vector beam characteristics has not been studied yet. Very recently, Zaïm ea al.…”
Section: Introductionmentioning
confidence: 99%
“…One way to reach even more extreme intensities is by focusing such bursts generated from self-generated 35 or manufactured 36,37 spherical or groove-shaped 29 plasma mirrors. Furthermore, recently discussed applications are related to the creation of compact sources of bright XUV pulses [38][39][40][41] with controllable ellipticity 42 and of bright gamma rays 43 emitted by the electrons in this regime of interaction. Since the generated XUV bursts can reach relativistic intensities for the XUV range of frequencies 44 , they can also be used for driving wakefields in solids 45,46 .…”
Section: Introductionmentioning
confidence: 99%